Novel missense variants in brain morphogenic genes associated with depression and schizophrenia - Karagyaur, Maxim; Primak, Alexandra; Bozov, Kirill; Sheleg, Dmitriy; Arbatsky, Mikhail; Dzhauari, Stalik; Illarionova, Maria; Semina, Ekaterina; Samokhodskaya, Larisa; Klimovich, Polina; Velichko, Arkadiy; Drach, Mikhail; et al. (Frontiers in Psychiatry, 2024)
Impaired function of brain morphogenic genes is considered one of the predisposing factors for the manifestation of psychiatric and cognitive disorders, such as paranoid schizophrenia (SCZ) and major depressive disorder (MDD). Identifying these genes, including neurotrophic factors and guidance molecules, and their deleterious genetic variants, is crucial for diagnosis, prevention, and possibly treatment of such disorders. This study examines the prevalence of genomic variants in brain morphogenic genes in individuals with SCZ and MDD in the Russian population. We conducted whole-exome sequencing of 21 DNA samples, consisting of 11 individuals with SCZ and 10 with MDD. Subsequently, we employed an Amplification-Refractory Mutation System (ARMS)-based screening method to examine the identified single nucleotide variants (SNVs) in larger cohorts: 102 individuals with SCZ, 79 with MDD, and 103 healthy donors. Whole-exome sequencing identified 226 missense mutations in 79 out of 140 studied genes. Some of these mutations occur more frequently in patients with psychiatric disorders than in healthy donors. New genomic variants in brain morphogenic genes, including CDH2 (rs1944294-T and rs17445840-T), DCHS2 (rs11935573-G and rs12500437-G/T), and CDH23 (rs1227051-G/A), have exhibited significant association with the incidence of SCZ and MDD in the Russian population. Of note, some single nucleotide variants (SNVs) like rs6265-T, rs1944294-T, rs11935573-G, and rs4760-G) displayed sex-biased differences in their prevalence between SCZ/MDD patients and healthy donors. However, the functional implications of these identified SNVs require validation through cellular and animal models. Once confirmed, these SNVs could enhance the diagnostic tools for assessing susceptibility to mental disorders. These findings indirectly emphasize the importance of proper brain structure formation for mental health preservation.